Dampak Psikologis Kecanduan Video Pendek pada Sekolah Dasar - Istamala, Mar'atus Sholihah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The advancement of digital technology has transformed children's media consumption patterns, marked by the growing use of short video content such as TikTok, YouTube Shorts, and Instagram Reels. This study aims to explore the psychological impacts of short video addiction on elementary school-aged children, focusing on cognitive, affective, and social aspects. Using a phenomenological qualitative approach, data were collected through in-depth interviews, observation, and documentation involving 10 children, 7 parents, and 4 teachers from two elementary schools. The findings indicate that children who intensively access short videos (more than two hours per day) experience reduced concentration, emotional instability, and social withdrawal. These results were analyzed using theoretical frameworks from Piaget (cognitive), Krathwohl (affective), Erikson and Bandura (social), and Young’s digital addiction model. The main conclusion reveals that short video addiction negatively affects children's developmental tasks, including logical thinking abilities, emotional regulation, and social skills. Therefore, digital literacy-based interventions and active supervision by parents and teachers are essential to prevent the long-term detrimental impacts on children's psychological development.